2010
DOI: 10.1021/ja1063444
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Metal−Hydrazone Complexes and Vapochromic Behavior of Their Hydrogen-Bonded Proton-Transfer Assemblies

Abstract: We synthesized and investigated a new series of metal-hydrazone complexes, including deprotonated [MX(mtbhp)] and protonated forms [MX(Hmtbhp)](ClO(4)) (M = Pd(2+), Pt(2+); X = Cl(-), Br(-); Hmtbhp = 2-(2-(2-(methylthio)benzylidene)hydrazinyl)pyridine) and hydrogen-bonded proton-transfer (HBPT) assemblies containing [PdBr(mtbhp)] and bromanilic acid (H(2)BA). The mtbhp hydrazone ligand acts as a tridentate SNN ligand and provides a high proton affinity. UV-vis spectroscopy revealed that these metal-hydrazone c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 79 publications
2
29
0
Order By: Relevance
“…In fact, Castellano and co‐workers reported a VOC‐sensing microarray composed of eighteen Pt II vapochromic complexes for distinct recognition of VOCs 84. Considering the recent remarkable progress in vapochromic materials including systems based on other noble metal ions,85102 non‐noble metal ions, [74–80,103–109] and organic molecules,110117 intelligent chemical‐sensing devices that can visually indicate environmental conditions will be achieved in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, Castellano and co‐workers reported a VOC‐sensing microarray composed of eighteen Pt II vapochromic complexes for distinct recognition of VOCs 84. Considering the recent remarkable progress in vapochromic materials including systems based on other noble metal ions,85102 non‐noble metal ions, [74–80,103–109] and organic molecules,110117 intelligent chemical‐sensing devices that can visually indicate environmental conditions will be achieved in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…We have focused our attention on the chromic behavior of these complexes. [12] We found that the protonation and deprotonation (proton-transfer) reaction of the N-H part on the coordinated hydrazone ligand plays an important role in the chromic behavior. [8][9][10][11] The photochromic behavior of hydrazones has been reported, [8] and some hydrazones induced E/Z isomerization by coordi-nating to a metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Recently, solid materials that exhibited color changes by vapor or gas absorption have attracted much attention. [15][16][17] The materials prepared in this study are liquid materials that exhibit reversible changes in color, thermal properties, and magnetic properties by the absorption and desorption of organic vapors and gases.…”
Section: Introductionmentioning
confidence: 99%